2021
DOI: 10.1177/2393957520983722
|View full text |Cite
|
Sign up to set email alerts
|

Mapping and Assessing Green Entrepreneurial Performance: Evidence from a Vertically Integrated Organic Beverages Supply Chain

Abstract: The purpose of this article is to use strategy mapping (SM) and balanced scorecard (BSC) in portraying and assessing green entrepreneurial supply chain management (GESCM) performance of a vertically integrated entrepreneurial supply chain in an Egyptian emerging market of organic beverages industry. Based on thematic literature review and qualitative research (in-depth interviews with experts, focus groups, observations, and reports’ analysis), multi-item measurement quantitative BSC scale and strategy map wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 92 publications
0
6
0
Order By: Relevance
“…Objective indexes may not get accurate results because they involve enterprise confidentiality. Thus, subjective indexes are easier to measure EP ( Adel, 2021 ; Lortie et al, 2021 ), including personal efficacy, employee satisfaction, and comparison with competitors. In summary, all methods can reflect the essential characteristics of entrepreneurship by measuring EP.…”
Section: Introductionmentioning
confidence: 99%
“…Objective indexes may not get accurate results because they involve enterprise confidentiality. Thus, subjective indexes are easier to measure EP ( Adel, 2021 ; Lortie et al, 2021 ), including personal efficacy, employee satisfaction, and comparison with competitors. In summary, all methods can reflect the essential characteristics of entrepreneurship by measuring EP.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the work of Claydon (2017) and Thomas and Pugh (2020), who supported harvesting the fruits of using quantitative and qualitative techniques in the data collection of social research, the authors followed a mixed-methods approach in the data gathering process as demonstrated in Figure 4. First, qualitative interviews were held to enhance the depth of understanding (Adel et al , 2018; Adel, 2021) of the promising USI practices executed in an emerging economy, especially during Covid-19 pandemic . A total of 30 qualitative in-depth individual interviews were set to gather data from managers/leaders and teaching staff working at those faculties in quality management processes and community engagement practices as well as students participating in USR activities.…”
Section: Methodsmentioning
confidence: 99%
“…Covin and Wales (2012) aggregated all the studies that conceptualised entrepreneurial orientation (EO) and contended that an activity is said to be entrepreneurial if it optimises promising business opportunities proactively through undertaking innovative strategies with calculated risk-taking behaviour. EO is operationalised in the literature (Adel et al, 2020;Niemand et al, 2021;Adel, 2021) through using three aspects (i.e. innovativeness, proactiveness and calculated risk-taking).…”
Section: Ijoem 1810mentioning
confidence: 99%